Some properties of branched continued fractions of special form - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2015)
The fact that the values of the approximates of the positive definite branched continued fraction of special form are all in a certain circle is established for the certain conditions. The uniform convergence of branched continued fraction of special form, which is a particular case of the mentioned fraction, in the some limited parabolic region is investigated.